Integration of Game-Based Learning in Interactive E-Books to Stimulate Collaborative Skills of Third Grade Elementary School Students - I Made Diah Pratiwi; Putu Aditya Antara; Dewi Anzelina (Universitas Pendidikan Ganesha, 2026)
The background of this study was the low level of students’ collaboration skills, as indicated by a collaboration questionnaire result with an average score of 58.4% in the moderate category, as well as the limited use of digital and interactive learning media in Pancasila Education learning. This study aimed to develop an interactive E-book based on Game-Based Learning that is feasible and effective in stimulating students’ collaboration skills in the topic of rights and responsibilities for third-grade elementary school students. This study employed a Research and Development (R&D) approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The research subjects included content experts, instructional design experts, learning media experts, and third-grade students. Data were collected through interviews, observations, questionnaires, and tests. The data were analyzed using descriptive quantitative and inferential analysis techniques. The results showed that the interactive E-book based on Game-Based Learning was categorized as very feasible based on expert validation and the results of individual and small-group trials. Furthermore, the effectiveness test results indicated an improvement in students’ collaboration skills after using the developed media, as proven by hypothesis testing. Therefore, the interactive E-book based on Game-Based Learning is considered feasible and effective to be used as a learning medium to stimulate students’ collaboration skills in Pancasila Education for third-grade elementary school students.